Frequency of Feeding on Body Weight and Chemical Levels of Local Goat Blood - Hamid, Padang; Zainal, Zainal; Nirwana, Nirwana; Mustafa, Mustafa (AgriSains, 2020)
This study aims to determine the body weight gain in the consumption of dry matter, the efficiency of the use of dry matter, blood glucose levels and blood urea levels of local goat which were fed with different frequencies. The test organisms were 15 local female goats aged 10 months and body weight of 14–20 kg. This research was an experimental study using a completely randomized design (CRD) with three treatments and 5 replications. The treatments tried were: P1 = Feeding 1.5% concentrate and 1.5% dry matter forage given once at 07.00 (UTC+8) based on body weight; P2 = 0.75% concentrate and 0.75% dry matter forage given at 07.00 (UTC+8), 13.00 (UTC+8) given 0.75% concentrate and 0.75% dry matter forage based on body weight; P3 = Feeding 0.5% concentrate and 0.5% forage dry matter is given at 07.00 (UTC+8), and at 13.00 (UTC+8) given 0.5% concentrate and 0.5% and at 19.00 (UTC+8) given 0.5% concentrate and 0.5% for dry matter based on body weight. The results of this study indicated that the frequency of feeding did not have an effect on dry matter consumption and blood urea levels, however, 2 times feeding significantly increased body weight gain, ration efficiency and blood glucose levels of local goat.